Gazing into the abyss?: making sense of extreme crime scene behaviors in sexual homicide - Beauregard, Eric (Routledge handbook of homicide studies, 2024)
The purpose of this chapter is to provide an overview of the available empirical knowledge on extreme crime scene behaviors observed in sexual homicides, namely foreign object insertion, overkill, dismemberment, necrophilic behaviors, and unusual behaviors. The first part defines the different extreme behaviors as well as describes the context in which they occur, and the factors associated with them. In the second part, this chapter is dedicated to the interpretation of the occurrence of these different behaviors by focusing on the motivations that led to their commission, in particular sadism and rationality. We conclude by suggesting some implications of these findings, especially for the criminal investigation.